Bond Strength of Glued-in Rods in Malaysian Tropical Timber as Influenced by Adhesive, Diameter and Glueline Thickness - N.E.L Za'ba; Z Ahmad; A Ibrahim (Universitas Gadjah Mada, 2012)
Failure in wood structure is mainly caused by improper connection design, construction (fabrication) details, or serviceability. Besides using traditional bolting methods such as nails, screws and bolts to join members, timber members also can be connected by using bonded-in joints. However, current knowledge in the use of this type of timber connection is still limited. This study investigated the performance of bonded-in pultruded rods in timber as connections by exploring the effect of a few parameters such as rod type, diameter of the rod, adhesive type and thickness of the glueline. Pull-out tests were used to characterize the strength of the bonded-in connections. From the results of this study, it was found that strength increased as glueline thickness increased, while strength decreasedas the diameter of the rod increased.